Ideological or pragmatic value-added capture? An inter-cantonal study on the influence of political legitimacy on the configuration of value-added capture in Switzerland - Scheiwiller, Louis; Hengstermann, Andreas (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
As one of the few examples worldwide, Swiss law serves for an instrument to compensate for planning-related increases in land value. The provision at the federal level however is not directly applicable, but merely a binding legislative mandate to the cantons. Beyond the minimum requirements under federal law, the cantons are given far-reaching discretion in the legislative process. This paper exploits this constellation in order to examine how the political legitimacy of the instrument affects the concrete legal configuration. Based on the planning literature, two schools of thought hold precedence. First, that pragmatic arguments would lead to farreaching cantonal regulations, e.g., through the explicit considerationof rezoning and upzoning as further taxable eventsin addition to the federal law requirement of zoning. Second, that ideological arguments are likely to only lead to minimal implementations, e.g., to a levy rate that does not exceed the minimum 20 percent prescribed by federal law. However, thiscomparative study based on the cantons of Basel-Stadt, Basel-Landschaft, and Bern instead points to a reverse correlation. In contrast to international experience, ideological arguments in Switzerland lead to amore far-reaching design of value added capture under planning law.
Keywords: Value-added capture; Policy analysis; Switzerland; Planning policy